A Preliminary Risk Assessment of Geomagnetically Induced Currents over the Italian Territory. Issue 1 (18th January 2019) - Tozzi, R.; De Michelis, P.; Coco, I.; Giannattasio, F.
Abstract: Geomagnetically induced currents (GICs), occurring as a result of space weather events, represent a hazard for the secure and safe operation of electrical power grids and oil/gas pipelines. The most exposed countries are those at high latitudes where, in the past, the occurrence of intense GICs has seriously damaged part of their power networks. However, very powerful space weather events have resulted in intense GICs also at middle and low latitudes. The G I C index is a proxy of the geoelectric field, and it can be estimated straightforwardly from magnetic observatory data. In this work, the G I C index is computed to investigate the possible impact of space weather events on the Italian territory. We first calculate the G I C index using data from the magnetic observatories of Castello Tesino, Duronia, and Lampedusa, together covering the whole Italian latitudinal extension, and show its behavior during the 2015 St. Patrick's day storm. Then, we consider measurements from the two longest running Italian magnetic observatories, that is, Castello Tesino and L'Aquila, and estimate the G I C index over more than 20 years of observations. A preliminary characterization of the general risk to which the Italian power grid network is exposed is given. Results show that during periods of high magnetic activity, potentially detrimental GICs could flow through the power network, especially at the highest Italian latitudes that are characterized by a low conductivity lithosphere. Key Points: GIC index is calculated using data from the two longest running Italian magnetic observatories for a time interval of almost two solar cycles The risk level for the Italian territory is estimated; results show that GICs can represent a hazard for Central and Northern Italy A wider census of failures in countries at middle magnetic latitudes is needed to better calibrate GIC index thresholds in those countries